2019
DOI: 10.15549/jeecar.v6i1.275
|View full text |Cite
|
Sign up to set email alerts
|

Bank deposit activity in Ukraine: Directions and factors of development activation

Abstract: Scientific-methodical approaches of identifying the main factors for attracting deposits in the Ukrainian banking system are presented in this paper. The author offers the following procedure: a comparative analysis of the long-term dynamics (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) of the placement of deposits in Ukrainian, Belarussian, and Polish banking systems as a result of socio-economic development trends in these countries; an estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Sobolieva-Tereshchenko (2018) conducted a comparative analysis of the Ukrainian bank card market, as well as its seven neighboring countries, and determined that the Ukrainian and Polish bank card markets are similar. Kichurchak (2019) described the directions and factors of the activation of the bank deposits market in Ukraine, determining the intensity of attraction of deposits to the banking systems of Ukraine, Belarus, and Poland.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…Sobolieva-Tereshchenko (2018) conducted a comparative analysis of the Ukrainian bank card market, as well as its seven neighboring countries, and determined that the Ukrainian and Polish bank card markets are similar. Kichurchak (2019) described the directions and factors of the activation of the bank deposits market in Ukraine, determining the intensity of attraction of deposits to the banking systems of Ukraine, Belarus, and Poland.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…In both countries, the portion of the corporate loan is much higher than the retail loans, as reported by the Central Bank of Russia and the National Bank of Ukraine. To revive the banking system and economic fundamentals, since 2016 host of reforms were introduced by both countries, like exchange rate reforms, inflation targeting, banking mergers, infusion of capital, and revocation of banking license (Financial development report, International Monetary Fund, 2019;Kichurchak, M.,2019). The International Monetary Fund suggested that due to the COVID-19 pandemic, both countries will face a recession in the near future, coupled with lower employment and consumer demand, which will eventually create a negative effect on debt service capabilities and banking profitability.…”
Section: Introductionmentioning
confidence: 99%